振動分光法により読み解くGPCRリガンド認識・シグナリングの正確性かつ自由性 - 片山, 耕大; 寿野, 良二; 神取, 秀樹; 魲, 洸平 (日本薬理学会年会要旨集, 2023)
GPCR signalling utilizes an allosteric coupling between the extracellular facing ligand-binding pocket and the cytoplasmic domain of the receptor that interacts with the signalling proteins. GPCR ligands impart different level of activation or deactivation of signalling proteins via GPCRs that are selectively and specifically regulated, in phenomena called ligand efficacy. The ligand efficacy remarkably affects the therapeutic properties of the ligand. Therefore, it is important to understand the molecular mechanism that determines the ligand efficacy in drug discovery research. Recently, we have attempted to use FTIR spectroscopy to study the conformational changes in muscarinic receptor (M2R) induced by ligand binding. The systematic ligand binding-induced difference FTIR spectroscopy on ligands with four different efficacies (agonist, partial agonist, antagonist, and inverse agonist) demonstrate the novel direct method for the quantitative evaluation of ligand efficacy on M2R. Notably, FTIR signals strongly correlates with the results of G-protein activity in cells. Thus, this approach emphasizes that the FTIR signal can serve as a probe to distinguish the ligand efficacy of M2R, and how FTIR spectroscopy can efficiently contribute to elucidate the underlying mechanism of ligand engagement and action towards the receptors.